Neo-Suprahepatic cava: A case report of a modified technique for domino liver transplantation - Padín, J. M. (2011)
Domino liver transplantation, introduced in 1997, originally consisted of a graft from a patient with familial amyloidotic polyneuropathy used as a donor for a compatible recipient, thus increasing the pool of hepatic grafts for liver transplantation. The aim of this report was to present a modification on the technique for outflow reconstruction in domino liver transplantation first proposed by Liu et al and Cescon et al. In this description we proposed a new technique that differs from the one mentioned above by performing a neo-suprahepatic cava, constructed using only an iliac vein graft, facilitating the anastomosis as if it was a regular cadaveric liver transplant.